Stellar tidal streams around nearby spiral galaxies with deep imaging from amateur telescopes - Martínez-Delgado, David; Stein, Michael; Sakowska, Joanna D.; Weigelt, M. Maurice; Román, Javier; Donatiello, Giuseppe; Roca-Fàbrega, Santi; Schirmer, Mischa; Grebel, Eva K.; Saifollahi, Teymoor; Kanipe, Jeff; Gómez-Flechoso, M. Angeles; et al. (Astronomy and astrophysics, 2025)
Context. Tidal interactions between massive galaxies and their satellites are fundamental processes in a universe with a Λ cold dark matter (ΛCDM) cosmology, and they redistribute material into faint features that preserve records of past galactic interactions. While stellar streams in the Local Group impressively demonstrate satellite disruption, they do not constitute a statistically significant sample. Constructing a substantial catalog of stellar streams beyond the Local Group remains challenging due to the difficulties in obtaining sufficiently deep wide-field images of galaxies. Despite their potential to illuminate dark matter distribution and galaxy formation processes overall, stellar streams remain underutilized as cosmological probes. Aims. The Stellar Tidal Stream Survey (STSS) addresses this observational gap by leveraging amateur telescopes to obtain deep scientific-grade images of galactic outskirts capable of building a more statistically meaningful sample of stellar streams. Methods. Over the past decade, the STSS has acquired deep (up to surface brightness limit ∼28.3 mag/arcsec2 in the r-band) wide-field images of 16 nearby Milky Way analog galaxies using a coordinated network of robotic amateur telescopes, which enabled the survey to avoid the issues associated with “mosaicking” smaller images taken with a single professional telescope. Results. Our survey revealed a diverse range of previously unreported faint features related to dwarf satellite accretion, including stellar streams, shells, and umbrella-like structures. We serendipitously discovered an ultra-diffuse galaxy (NGC150-UDG1) that shows hints of tidal tails. Conclusions. The STSS demonstrates the suitability of modern amateur telescopes to detect and study faint, diffuse structures in large fields around nearby spiral galaxies. Their economic and accessibility advantages enable larger statistical samples with deep imaging, which are essential for testing galaxy formation models and constraining the frequency and properties of minor merger events in the local Universe.
Gesehen am 20.01.2026